Identification of She3 as an SCF(Grr1) Substrate in Budding Yeast - Wang, Ruiwen (Public Library of Science, 2012)
The highly orchestrated progression of the cell cycle depends on the degradation of many regulatory proteins at different cell cycle stages. One of the key cell cycle ubiquitin ligases is the Skp1-cullin-F-box (SCF) complex. Acting in concert with the substrate-binding F-box protein Grr1, SCF(Grr1) promotes the degradation of cell cycle regulators as well as various metabolic enzymes. Using a yeast two-hybrid assay with a Grr1 derivative as the bait, we identified She3, which is an adaptor protein in the asymmetric mRNA transport system, as a novel Grr1 substrate. We generated stabilized She3 mutants, which no longer bound to Grr1, and found that the degradation of She3 is not required for regulating asymmetric mRNA transport. However, She3 stabilization leads to slower growth compared to wild-type cells in a co-culture assay, demonstrating that the degradation of She3 by Grr1 is required for optimal cell growth.